2015
DOI: 10.1088/1748-3190/10/4/046015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of a dual configuration for a flapping tidal current generator

Abstract: In this study, we conduct experimental and consecutive numerical analyses of a flapping tidal current generator with a mirror-type dual configuration with front-swing and rear-swing flappers. An experimental analysis of a small-scale prototype is conducted in a towing tank, and a numerical analysis is conducted by means of two-dimensional computational fluid dynamics simulations with an in-house code. An experimental study with a controller to determine the target arm angle shows that the resultant arm angle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In the following sub-sections, three sets of fluid dynamics simulations are described. These cases are typical fluid dynamics problems commonly studied in literature, and are used here as a basis for comparing the performance of the U-Net model and the proposed U-Net-MG model (Jihoon Kim et al, 2015;Mahir & Rockwell, 1996;Ooi et al, 2020;Read et al, 2003). All simulations are run via the opensource OpenFOAM platform with the k-ω SST turbulence model.…”
Section: Cfd Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following sub-sections, three sets of fluid dynamics simulations are described. These cases are typical fluid dynamics problems commonly studied in literature, and are used here as a basis for comparing the performance of the U-Net model and the proposed U-Net-MG model (Jihoon Kim et al, 2015;Mahir & Rockwell, 1996;Ooi et al, 2020;Read et al, 2003). All simulations are run via the opensource OpenFOAM platform with the k-ω SST turbulence model.…”
Section: Cfd Simulation Resultsmentioning
confidence: 99%
“…In the following sections, we present our results on the following fluid dynamical systems: 1) flow past a stationary cylinder, and flow due to two cylinders in out-of-phase motion; and 2) flow past an oscillating foil. These examples are chosen as the former set of scenarios are commonly studied canonical problems in fluid dynamics, with relevance to the marine industry such as in understanding the interaction between risers (Hu & Zhou, 2008;Huera-Huarte & Jiménez-González, 2019;Liu & Jaiman, 2016;Wang, Xiao, Zhu, & Incecik, 2017), while the latter set of scenarios are greatly relevant to the areas of propulsion or energy harvesting (Andersen, Bohr, Schnipper, & Walther, 2017;Jihoon Kim et al, 2015;Kinsey & Dumas, 2008;Read, Hover, & Triantafyllou, 2003). Critically, they also encompass an interesting range of problems in surrogate modeling, including flow in a scenario with a fixed object and constant boundary conditions (flow past a stationary cylinder), flow in a scenario with varying inlet boundary conditions and moving objects (flow past two cylinders in out-of-phase motion), and flow in a scenario with consistent inlet boundary conditions and moving objects but with varying geometries (flow past oscillating foils of different geometries).…”
Section: Introductionmentioning
confidence: 99%
“…They found that it is possible to improve performance of an oscillating foil system through multi-stage foils arranged in tandem form. Kim et al 29 carried out experimental and consecutive numerical analyses of an oscillating tidal current generator with front-swing and rear-swing flappers. They concluded that the oscillating foil micro-hydropower generator has significant further development potential.…”
Section: Introductionmentioning
confidence: 99%
“…28 The experiments confirmed the competitive performance of the oscillating foil hydrokinetic turbine compared to rotor-blade designs. Kim et al 29 carried out experimental and consecutive numerical analyses of an oscillating tidal current generator with front-swing and rear-swing flappers.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the semi-empirical model of the dynamic stall is effective in predicting the aerodynamic force and efficiency. The numerical research on the extraction performance of foil discusses the potential effect factors like the oscillation motion, the motion parameter, the Re number and the profile of foil by the control variable method and the traditional optimization algorithm, aiming at finding a higher power output and extraction efficiency [6][7][8][9][10][11][12][13]. The oscillation process always adopts the sinusoidal motion, however, some researchers tried to use non-sinusoidal motion on foil for further investigations.…”
Section: Introductionmentioning
confidence: 99%